Pemodelan Matematika SIRI pada Penyebaran Penyakit Tifus di Sulawesi Selatan - Side, Syafrudin; Zaki, Ahmad; Sartika, Sartika (Jurusan Matematika FMIPA UNM, 2021)
The research aims to build a SIRI model of the Typhoid spread (Susceptible-Infected-Recovered-Infected) by adding assumption that people who are recovered might be infected again. This model is divided into three classes, namely, susceptible, infected and recovered. the research procedure is carried out through several stages: Building SIRI model for the spread of Typhoid, examining the stability of the equilibrium point and determining the basic reproduction number, and applying the model to Typhoid cases in South Sulawesi. The data is the number of Typhus patients in 2018 that was obtained from Health office of South Sulawesi Province. SIRI type mathematical models are used to determine the equilibrium point. Based on the simulation results of the SIRI model, the basic reproduction number is 0,000903 indicate that, indicating that the spread of Typhus in the Province of South Sulawesi in 2018 was not an extraordinary event or it can be said that someone who is infected with this Typhoid does not cause another person to contract the same disease, in other words there was no outbreak in that population.